2014
DOI: 10.1063/1.4871482
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials synthesis by a novel phenomenon: The nanoscale Rayleigh-Taylor instability

Abstract: The Rayleigh-Taylor (RT) interfacial instability has been attributed to physical phenomenon in a wide variety of macroscopic systems, including black holes, laser generated plasmas, and thick fluids. However, evidence for its existence in the nanoscale is lacking. Here we first show theoretically that this instability can occur in films with thickness negligible compared to the capillary length when they are heated rapidly inside a bulk fluid. Pressure gradients developed in the evaporated fluid region produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…Figure 64 summarizes some outlooks for the pulsed-laser use in nanostructuration. In this sense, the use of interfering lasers [31,61] of the pulsed-laser processing of metal films in liquids exploiting the Rayleigh-Taylor phenomenon [144,145] and the pulsed-laser processing of multielement (as alloyed) films or multilayered metallic films [146,147,148,149] will be the key approaches. In particular, in this last case, alloyed and multi-elemental nanostructures can be produced with innovative properties arising from the synergistic combination of the properties of the metallic components.…”
Section: Conclusion Perspectives and Challengesmentioning
confidence: 99%
“…Figure 64 summarizes some outlooks for the pulsed-laser use in nanostructuration. In this sense, the use of interfering lasers [31,61] of the pulsed-laser processing of metal films in liquids exploiting the Rayleigh-Taylor phenomenon [144,145] and the pulsed-laser processing of multielement (as alloyed) films or multilayered metallic films [146,147,148,149] will be the key approaches. In particular, in this last case, alloyed and multi-elemental nanostructures can be produced with innovative properties arising from the synergistic combination of the properties of the metallic components.…”
Section: Conclusion Perspectives and Challengesmentioning
confidence: 99%
“…[ 13,14,18 ] In addition, the technique can potentially be benefi ted by the recent advancements in PLDew under liquids where even smaller NSs ≈10 nm are synthesized. [ 21 ] These results collectively conveyed that the proposed synthesis route is able to produce Ag NSs with a monomodal size distribution and wide range of NS diameters over a reasonably large area (≈3 mm). (Figure 3 a), elliptical-shaped NSs following 50 pulses (Figure 3 b), and fi nally, hemispherical-shaped NSs after 100 pulses (Figure 3 c).…”
Section: Large-area Coverage Of Nssmentioning
confidence: 59%
“…However, it principally can duplicate any NS size ranges reported on inert SiO 2 substrate; i.e., 20–200 nm for single metallic NSs and 25–350 nm for bimetallic NSs . In addition, the technique can potentially be benefited by the recent advancements in PLDew under liquids where even smaller NSs ≈10 nm are synthesized . These results collectively conveyed that the proposed synthesis route is able to produce Ag NSs with a monomodal size distribution and wide range of NS diameters over a reasonably large area (≈3 mm).…”
Section: Resultsmentioning
confidence: 80%
“…Symbiosis in Plasmonic Nanoparticles http://dx.doi.org/10.5772/intechopen.71730 related research requiring energy hotspots. Recently, Yadavali and Kalyanaraman reported that the particle spacing of the nanoparticles can be independent of the initial film thickness which is not the case in classical spinodal dewetting by creating Rayleigh-Taylor instabilities at the metal film surface in contact with liquid creating large pressure gradients due to evaporation [14].…”
Section: Pulsed Laser Induced Dewetting (Plid)mentioning
confidence: 99%